The Role of Autophagy in Skeletal Muscle Diseases - Xia, Qianghua; Huang, Xubo; Huang, Jieru; Zheng, Yongfeng; March, Michael E.; Li, Jin; Wei, Yongjie (Frontiers in Physiology, 2021)
Skeletal muscle is the most abundant type of tissue in human body, being involved in diverse activities and maintaining a finely tuned metabolic balance. Autophagy, characterized by the autophagosome–lysosome system with the involvement of evolutionarily conserved autophagy-related genes, is an important catabolic process and plays an essential role in energy generation and consumption, as well as substance turnover processes in skeletal muscles. Autophagy in skeletal muscles is finely tuned under the tight regulation of diverse signaling pathways, and the autophagy pathway has cross-talk with other pathways to form feedback loops under physiological conditions and metabolic stress. Altered autophagy activity characterized by either increased formation of autophagosomes or inhibition of lysosome-autophagosome fusion can lead to pathological cascades, and mutations in autophagy genes and deregulation of autophagy pathways have been identified as one of the major causes for a variety of skeleton muscle disorders. The advancement of multi-omics techniques enables further understanding of the molecular and biochemical mechanisms underlying the role of autophagy in skeletal muscle disorders, which may yield novel therapeutic targets for these disorders.